La sympoliteia griega en las épocas clásica y helenística - Pascual, José (Gerión. Revista de Historia Antigua, 2008)
This paper attempts to analyse the Greek Sympoliteia in the Classical and Hellenistic periods. The Sympoliteia as participation in the essential elements of the citizenship (political and judicial institutions, sacrifices and public cults) could be applied within the own polis or state (fellow-citizens), in a multilateral context (federal sympoliteia or confederacy), or bilateral (federal sympoliteia or tending to the unification) and it could be also related to the interchange of citizenship between two states.